Development of higher order thinking skill assessment instruments in social studies learning - Nurizky Handayani; Suranto Aw; Zamroni Zamroni; Myristica Imanita; Johan Setiawan; Muhammad Rijal Fadli (International Journal of Evaluation and Research in Education (IJERE), 2024)
Higher order thinking skill (HOTS) in social studies learning are still often ignored by teachers despite the need for students to acquire these skills. The purpose of this study is to develop her HOTS assessment in a social studies classroom to help teachers improve their students’ thinking skills. This kind of research is research and development with 4D models. Validation was performed by two social studies learning assessment specialists and three social studies teachers. The HOTS test was administered to 112 students in class VIII (second grade) of Yogyakarta junior high school. Data analysis consisted of validity, reliability, difficulty, selectivity, and distractor index. Explanatory factor analysis (EFA) pathway analysis was used for data analysis of small trials and confirmatory factor analysis (CFA) pathway analysis was used for large trials. The multiple-choice HOTS assessment tool consisted of 30 items, and the effectiveness results of this HOTS questions on material, structure, and language aspects by two social studies learning assessment experts where it was valid and suitable for our application. Effective results for three social studies teachers indicated that the assessment tool was valid and applicable. HOTS in social studies learning helps improve quality and learning outcomes, enabling students to examine information critically, develop creativity, and improve problem-solving skills.